2017
DOI: 10.1073/pnas.1618627114
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein binds and sequesters PIKE-L into Lewy bodies, triggering dopaminergic cell death via AMPK hyperactivation

Abstract: The abnormal aggregation of fibrillar α-synuclein in Lewy bodies plays a critical role in the pathogenesis of Parkinson's disease. However, the molecular mechanisms regulating α-synuclein pathological effects are incompletely understood. Here we show that α-synuclein binds phosphoinositide-3 kinase enhancer L (PIKE-L) in a phosphorylationdependent manner and sequesters it in Lewy bodies, leading to dopaminergic cell death via AMP-activated protein kinase (AMPK) hyperactivation. α-Synuclein interacts with PIKE-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…However, the relationship between AMPK and αSyn is not straightforward. Some studies have noted that αSyn decreases AMPK phosphorylation at Thr172 [187], while others have observed that αSyn increases it [189]. One possible explanation for these contradictory findings is that αSyn and phosphorylated αSyn differentially affect AMPK.…”
Section: Ampk Activation As a Treatment Strategy For Pdmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the relationship between AMPK and αSyn is not straightforward. Some studies have noted that αSyn decreases AMPK phosphorylation at Thr172 [187], while others have observed that αSyn increases it [189]. One possible explanation for these contradictory findings is that αSyn and phosphorylated αSyn differentially affect AMPK.…”
Section: Ampk Activation As a Treatment Strategy For Pdmentioning
confidence: 99%
“…Unphosphorylated αSyn activates the phosphatase PP2A, which promotes the dephosphorylation of both αSyn and AMPK, whereas pS129-αSyn inhibits PP2A [192,193]. Furthermore, pS129-αSyn was found to sequester PIKE-L, an inhibitor of AMPK, leading to increased AMPK activity in mice and in SH-SY5Y cells overexpressing αSyn [189]. Thus, unphosphorylated αSyn may inhibit AMPK function through PP2A, but as αSyn becomes increasingly phosphorylated this inhibition declines and other AMPK regulating proteins become inhibited, leading to increased AMPK activity [193].…”
Section: Ampk Activation As a Treatment Strategy For Pdmentioning
confidence: 99%
See 3 more Smart Citations